(untitled) (Mediscope, 2021)
Coronavirus disease 2019 (COVID-19) an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first identified in 2019 in Wuhan, the capital of China’s Hubei province, and has eventually spread to the size of pandemic. This article points outs the facts of its epidemiology and management in a thoughtful, brief, palatable, revealing and innovative way. This article also discusses a few innovations which could make the environment unfriendly to SARS-CoV-2. Mediscope Vol. 8, No. 1: January 2021, Page 53-62